Reverse logistics adoption among Malaysian manufacturers - Nik Abdullah, Nik Ab. Halim; Yaakub, Sabariah; Abdullah, Haim Hilman (2011)
This paper presents the descriptive analysis of a study on the reverse logistics adoption among manufacturers in Malaysian.The objective of this paper is to investigate the current state or level of reverse logistics adoption by Malaysian manufacturers, the reverse logistics activities performed and the strategic benefits of adopting reverse logistics.Another focus is on the barriers faced by companies in implementing reverse logistics activities in their operation.Data were collected through survey questionnaires that were distributed via mail, e-mail or self administered.A total of 101 usable responds were received and analyzed. Findings indicate that reverse logistics activities have been implemented by all respondents but the level of adoption are relatively very low.This lower than average level of adoption can be attributed to the fact that manufacturers are lacking in terms of knowledge and awareness on reverse logistics concept, together with the perception that reverse logistics are expensive and requires huge resources to implement.Discussions on the findings, significance of the study and direction for future research are then discussed.